Preparation method of tungsten-based composite material with high hardness, low oxygen content and net-shaped grain boundary pinning structure

Through argon-filled powder mixing and discharge plasma sintering technology, a tungsten-boron composite material with high hardness, low oxygen content and mesh grain boundary pinning structure was prepared, which solved the problem of oxidation of tungsten-based materials during mechanical alloying and significantly improved the performance of the material.

CN119506636AActive Publication Date: 2025-02-25HEFEI UNIV OF TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411685982.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-24
Publication Date
2025-02-25
Estimated Expiration
2044-11-24

AI Technical Summary

Technical Problem

Tungsten-based materials are easily oxidized during mechanical alloying, resulting in segregation of oxygen at grain boundaries and reducing the grain boundary bonding force and comprehensive mechanical properties of the material.

Method used

The W-B composite powder was prepared by argon-filled powder mixing method, and through discharge plasma sintering technology, boron element and oxygen element at the tungsten crystal boundary form a low-melting compound, which evaporates at high temperatures to reduce the oxygen element concentration.

Benefits of technology

It significantly improves the hardness and density of tungsten-based composite materials, reduces the oxygen content, forms a mesh grain boundary pinning structure, and enhances grain boundary binding force.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119506636A_ABST
    Figure CN119506636A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a tungsten-based composite material with high hardness, low oxygen content and a net-shaped grain boundary pinning structure, and relates to the technical field of tungsten-boron composite material preparation. The preparation method comprises the following steps: firstly, obtaining W-B composite powder by adopting a method of argon filling and mixing of a mixer, and then preparing the W-B tungsten-based composite material through optimization of spark plasma sintering and regulation and control of a grain boundary structure. The boron element and the oxygen element at the tungsten grain boundary are combined in the spark plasma sintering process to form a low-melting-point compound, the compound is evaporated at high temperature, the concentration of the oxygen element is reduced, and the weakening effect of O on the cohesion of the grain boundary is reduced. The relative density of the prepared W-B tungsten-based composite material reaches 95.0% or above, the microhardness value reaches 493.2-697.4 HV, and the W-B tungsten-based composite material is superior to a pure tungsten material (the microhardness is 360-420 HV). Meanwhile, the oxygen content (4.0-32.4 ppm) is obviously lower than the oxygen content (124.6-248.9 ppm) of the tungsten-boron composite material prepared by high-energy mechanical ball milling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of tungsten-boron composite materials, and in particular to a method for preparing a tungsten-based composite material with high hardness, low oxygen content and a network grain boundary pinning structure. Background Art

[0002] Tungsten (W) has a high melting point (3683K), high density (19.3g.cm -3 )、High thermal conductivity (174W(mk) -1 ), low thermal expansion coefficient (4.5x10 -6 K -1 ) and low sputtering threshold, and is considered the most promising plasma-facing materials (PFMs) in fusion devices. In the magnetic confinement nuclear fusion device (ITER), PFMs must withstand harsh service conditions such as high heat load, plasma impact, and neutron irradiation. Under these conditions, the material will suffer serious damage, such as cracking, melting, and blistering, which seriously affect the operation of the reactor.

[0003] However, the inherent brittleness of tungsten is an important cause of these damages. The BCC crystal structure with high Peierls stress and poor grain boundary cohesion cause the low-temperature limited plasticity of tungsten. One of the main reasons for the low-temperature limited plasticity of refractory metals such as tungsten and molybdenum is the high sensitivity of the material to interstitial impurities. These impurities tend to segregate at the grain boundaries, reduce the grain boundary cohesion, and cause grain boundary brittleness.

[0004] Therefore, researchers considered adding grain boundary cohesion enhancers to tungsten-based materials to remove oxygen, a brittle element at the grain boundaries, and further improve the grain boundary bonding strength of the material. The current strategy to reduce the concentration of free oxygen at the grain boundaries is mainly to add active elements that easily form stable compounds with oxygen, such as titanium (Ti), zirconium (Zr), and hafnium (Hf). Researchers have shown through simulation calculations that boron (B) has the highest strengthening potential at tungsten grain boundaries and is a very effective grain boundary cohesion enhancer. Boron can potentially remove and replace oxygen at the grain boundaries at the tungsten grain boundaries, improve the grain boundary bonding strength of the material, and thus strengthen the tungsten grain boundaries.

[0005] Mechanical ball milling is one of the effective means to design the structure of materials. It can adjust the desired structure and performance, and is particularly suitable for the preparation of nanomaterials. However, the powder is easily oxidized due to local overheating during the mechanical alloying collision process, which causes oxygen segregation at the grain boundary during the subsequent sintering process, resulting in deterioration of material performance. Therefore, reducing the oxygen content of the material and preparing tungsten-based composite materials with excellent comprehensive mechanical properties is a hot topic for researchers. Summary of the invention

[0006] In order to solve the problem that mechanical ball milling is easy to achieve material structure regulation and preparation of multi-element powders, but introduces defects such as oxygen impurities during the mechanical alloying process, the present invention proposes a preparation method of a tungsten-based composite material with high hardness, low oxygen content and a network grain boundary pinning structure. Firstly, a mixer is used to mix powders with argon to obtain WB composite powders, and then the WB tungsten-based composite material is prepared by optimizing spark plasma sintering and regulating the grain boundary structure, so as to significantly improve the hardness of the tungsten-based composite material and reduce its oxygen content.

[0007] In order to achieve the above-mentioned purpose, the technical solution adopted by the present invention is:

[0008] A method for preparing a tungsten-based composite material with high hardness, low oxygen content and a network grain boundary pinning structure, comprising the following steps:

[0009] Step 1: Flour making:

[0010] W powder, B powder and an appropriate amount of WC cemented carbide balls are placed in a plastic solid bottle according to the proportion, filled with argon in a glove box, sealed and placed in a mixer for powder mixing; after mixing, the composite powder is vacuumed and stored to obtain WB composite powder;

[0011] Step 2: Powder filling:

[0012] The WB composite powder obtained in step 1 is filled into the graphite mold. Before the mold is filled with powder, carbon paper needs to be rolled evenly, and the carbon paper is tightly attached to the inner wall of the mold, and the distance between the upper and lower punches and the mold is just filled with carbon paper; the upper and lower punches are adjusted so that the powder is located in the center of the mold; the mold filled with powder is pre-pressed under a tablet press; the pre-pressed mold is assembled with thermal insulation carbon felt, and the temperature measuring hole of the mold is adjusted to align with the reserved hole of the thermal insulation carbon felt;

[0013] Step 3: Spark plasma sintering:

[0014] The graphite mold filled with the powder in step 2 is placed in a spark plasma sintering furnace chamber, and the furnace chamber is evacuated; sintering is started to prepare a tungsten-boron composite material block, that is, a tungsten-based composite material with high hardness, low oxygen content and a network grain boundary pinning structure.

[0015] As a preferred technical solution of the present invention, in the preparation method:

[0016] In step 1, the proportion of B powder is 0.5-1.0% by mass percentage, and the balance is W powder. The argon filling pressure in the plastic solid bottle is 0.01-0.02 MPa. The speed of the mixer is 50-60 rpm, and the mixing time of W powder and B powder is 10-15 hours. The diameter of the WC cemented carbide ball is 4-6 mm, and the product of the number of added WC cemented carbide balls and their diameter is 2 / 3 of the height of the plastic solid bottle, and the obtained number is the number of WC cemented carbide balls added.

[0017] In step 2, the mass of the loaded WB composite powder is 12-18 g. The size of the loaded carbon paper is 12.7 mm long, 3-4 mm wider than the mold length, and 0.1 mm thick. The mold pre-pressing pressure is 5 MPa, and the pre-pressing time is 3-5 min. The assembled carbon felt thickness is 0.5 mm.

[0018] In step 3, after the furnace chamber is evacuated, the vacuum degree is 10Pa. The specific steps of spark plasma sintering are: heating to 1300℃ at 100℃ / min and keeping warm for 5-10min, then heating to 1600-1700℃ at 100℃ / min and keeping warm for 5min; after the insulation is completed, stop heating immediately, cool to room temperature with the furnace, and obtain a tungsten-boron composite material block after demolding. The load borne by the mold during the spark plasma sintering process is 0.5t.

[0019] Compared with the prior art, the beneficial effects of the present invention are mainly manifested in:

[0020] 1. Under the raw material ratio and sintering process parameters specified in the present invention, the WB composite powder is obtained by the argon filling powder mixing method, and then the WB composite material block with a network grain boundary pinning structure can be obtained by the spark plasma sintering technology. Boron element combines with oxygen element at the tungsten grain boundary during the spark plasma sintering process to form a low melting point compound, which evaporates at high temperature, reduces the concentration of oxygen element, and reduces the weakening effect of O on the grain boundary cohesion.

[0021] 2. The WB tungsten-based composite material prepared by the present invention has a relative density of more than 95.0%, and a microhardness value of 493.2-697.4 HV, which is better than pure tungsten material (microhardness 360-420 HV). At the same time, the oxygen content of the WB tungsten-based composite material prepared by the present invention is 4.0-32.4 ppm, which is significantly lower than the oxygen content of the tungsten-boron composite material prepared by high-energy mechanical ball milling (124.6-248.9 ppm). BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1This is a SEM of the W-1.0wt.%B tungsten-based composite material block prepared by spark plasma sintering in Example 1; (a) is the fracture morphology, and (b) is the network second phase pinning structure at the grain boundary of the fracture. It can be seen that a tungsten-based composite material with a network second phase pinning structure and grain boundary reinforcement is prepared.

[0023] Figure 2 a, b, and c are metallographic images of the W-xB tungsten-based composite materials prepared by spark plasma sintering in Examples 1, 2, and 3. It can be seen that the volume fraction of the second phase in the W-xB tungsten-based composite material increases with the increase in the addition amount of the B element.

[0024] Figure 3 The relative density and microhardness of the W-xB tungsten-based composite materials prepared after spark plasma sintering in Examples 1, 2, and 3. It can be seen that the densification temperature of the W-xB tungsten-based composite materials increases with the increase of the addition amount of the B element, and the hardness of the W-xB tungsten-based composite materials increases with the increase of the addition amount of the B element. DETAILED DESCRIPTION

[0025] The present invention is further described in detail below in conjunction with embodiments and drawings.

[0026] Embodiment 1:

[0027] In the method for preparing the low-oxygen and high-hardness WB tungsten-based composite material in this embodiment, the ratio of W powder to B powder is 1.0% by mass of B powder and the remainder is W powder, and the steps are as follows:

[0028] 1. Powder making: Mix W powder (0.5 μm, Xiamen Jinlu Special Alloy Co., Ltd.) and B powder (D 50 =10-20μm, Aladdin, purity ≥99%) and an appropriate amount of WC carbide balls are loaded into a 100mL plastic solid bottle; the plastic solid bottle is filled with argon in a glove box, and the argon pressure in the bottle is 0.02MPa; the argon-filled solid bottle is sealed; the sealed solid bottle is placed in a mixer for powder mixing, the mixer speed is 60rpm, and the mixing time is 12h; the mixed composite powder is vacuumed and stored to obtain WB composite powder.

[0029] 2. Powder filling: Fill 15g of the WB composite powder obtained in step 1 into a graphite mold with an inner diameter of 20mm. Before filling the mold with powder, a piece of 0.1mm thick carbon paper needs to be evenly rolled and spread. The carbon paper fits tightly against the inner wall of the mold, and the distance between the upper and lower punches and the mold is just filled with carbon paper; adjust the position of the upper and lower punches so that the powder is located in the center of the mold; pre-press the powder-filled mold under a tablet press with a pre-pressing pressure of 5MPa and a pre-pressing time of 5min; assemble the pre-pressed mold with insulating carbon felt with a thickness of 0.5mm, and adjust the mold temperature measuring hole to align with the reserved hole of the insulating carbon felt.

[0030] 3. Spark plasma sintering: Place the graphite mold filled with powder in step 2 in the spark plasma sintering furnace chamber, and evacuate the furnace chamber (10Pa); after starting sintering, heat to 1300℃ at 100℃ / min and keep warm for 10min, then heat to 1700℃ at 100℃ / min and keep warm for 5min; after the insulation is completed, stop heating immediately, cool to room temperature with the furnace, and obtain a tungsten-boron composite material block after demolding (the load borne by the mold during the sintering process is 0.5t).

[0031] Comparative Example 1:

[0032] 1. High-energy mechanical ball milling:

[0033] W powder, B powder and WC carbide balls are loaded into a ball mill, and then an appropriate amount of process control agent anhydrous ethanol is added to the mixed powder; the ball mill is filled with argon and the ball milling parameters are set for ball milling: the ball milling speed is 400 rpm, and the ball milling time is 12 h; the slurry after ball milling is dried to obtain WB composite powder; based on the mass percentage of the mixed powder, the proportion of B powder is 1.0%, and the balance is W powder.

[0034] 2. Powder filling: same as step 2 of Example 1.

[0035] 3. Powder filling: same as step 3 of Example 1.

[0036] See also Figures 1 to 3 As shown, the W-1.0wt.%B composite material prepared by spark plasma sintering in Example 1 can obtain a network second phase pinning structure at the grain boundary, which increases the grain boundary bonding force. The addition of B element also reduces the oxygen content in the matrix material. The oxygen content of the W-1.0wt.%B composite material is 24.0ppm, which is lower than the oxygen content of the W-1.0wt.%B composite material prepared by high-energy mechanical ball milling in Comparative Example 1 (124.6ppm).

[0037] Meanwhile, the W-1.0wt.%B tungsten-based composite material prepared by sintering at 1700°C in Example 1 has a relative density of 99.9% and a microhardness of 672.1±15.6HV, which is better than pure tungsten material (microhardness 360-420HV).

[0038] Embodiment 2:

[0039] In the method for preparing the low-oxygen and high-hardness WB tungsten-based composite material in this embodiment, the ratio of W powder to B powder is 1.0% by mass of B powder and the remainder is W powder, and the steps are as follows:

[0040] 1. Powder making: Mix W powder (0.5 μm, Xiamen Jinlu Special Alloy Co., Ltd.) and B powder (D 50 =10-20μm, Aladdin, purity ≥99%) and an appropriate amount of WC carbide balls are loaded into a 100mL plastic solid bottle; the plastic solid bottle is filled with argon in a glove box, and the argon pressure in the bottle is 0.02MPa; the argon-filled solid bottle is sealed; the sealed solid bottle is placed in a mixer for powder mixing, the mixer speed is 60rpm, and the mixing time is 12h; the mixed composite powder is vacuumed and stored to obtain WB composite powder.

[0041] 2. Powder filling: Fill 15g of the WB composite powder obtained in step 1 into a graphite mold with an inner diameter of 20mm. Before filling the mold with powder, a piece of 0.1mm thick carbon paper needs to be evenly rolled and spread. The carbon paper fits tightly against the inner wall of the mold, and the distance between the upper and lower punches and the mold is just filled with carbon paper; adjust the position of the upper and lower punches so that the powder is located in the center of the mold; pre-press the powder-filled mold under a tablet press with a pre-pressing pressure of 5MPa and a pre-pressing time of 5min; assemble the pre-pressed mold with insulating carbon felt with a thickness of 0.5mm, and adjust the mold temperature measuring hole to align with the reserved hole of the insulating carbon felt.

[0042] 3. Spark plasma sintering: Place the graphite mold filled with powder in step 2 in the spark plasma sintering furnace chamber, and evacuate the furnace chamber (10Pa); after starting sintering, heat to 1300℃ at 100℃ / min and keep warm for 10min, then heat to 1600℃ at 100℃ / min and keep warm for 5min; after the insulation is completed, stop heating immediately, cool to room temperature with the furnace, and obtain a tungsten-boron composite material block after demolding (the load borne by the mold during the sintering process is 0.5t).

[0043] Comparative Example 2:

[0044] 1. High-energy mechanical ball milling:

[0045] W powder, B powder and WC carbide balls are loaded into a ball mill, and then an appropriate amount of process control agent anhydrous ethanol is added to the mixed powder; the ball mill is filled with argon and the ball milling parameters are set for ball milling: the ball milling speed is 400 rpm, and the ball milling time is 12 h; the slurry after ball milling is dried to obtain WB composite powder; based on the mass percentage of the mixed powder, the proportion of B powder is 1.0%, and the balance is W powder.

[0046] 2. Powder filling: same as step 2 in Example 2.

[0047] 3. Powder filling: same as step 3 in Example 2.

[0048] See also Figures 1 to 3 As shown, the W-1.0wt.%B composite material prepared by spark plasma sintering in Example 2 can obtain a network second phase pinning structure at the grain boundary, which increases the grain boundary bonding force. The addition of B element also reduces the oxygen content in the matrix material. The oxygen content of the W-1.0wt.%B composite material is 24.6ppm, which is lower than the oxygen content (126.8ppm) of the W-1.0wt.%B composite material prepared by high-energy mechanical ball milling in Comparative Example 2.

[0049] Meanwhile, the W-1.0wt.%B tungsten-based composite material prepared by sintering at 1600°C in Example 2 has a relative density of 95.9% and a microhardness of 526.6±18.8HV, which is better than pure tungsten material (microhardness 360-420HV).

[0050] Embodiment 3:

[0051] In the method for preparing the low-oxygen and high-hardness WB tungsten-based composite material in this embodiment, the ratio of W powder to B powder is 0.5% by mass of B powder and the remainder is W powder, and the steps are as follows:

[0052] 1. Powder making: Mix W powder (0.5 μm, Xiamen Jinlu Special Alloy Co., Ltd.) and B powder (D 50 =10-20μm, Aladdin, purity ≥99%) and an appropriate amount of WC carbide balls are loaded into a 100mL plastic solid bottle; the plastic solid bottle is filled with argon in a glove box, and the argon pressure in the bottle is 0.02MPa; the argon-filled solid bottle is sealed; the sealed solid bottle is placed in a mixer for powder mixing, the mixer speed is 60rpm, and the mixing time is 12h; the mixed composite powder is vacuumed and stored to obtain WB composite powder.

[0053] 2. Powder filling: Fill 15g of the WB composite powder obtained in step 1 into a graphite mold with an inner diameter of 20mm. Before filling the mold with powder, a piece of 0.1mm thick carbon paper needs to be evenly rolled and spread. The carbon paper fits tightly against the inner wall of the mold, and the distance between the upper and lower punches and the mold is just filled with carbon paper; adjust the position of the upper and lower punches so that the powder is located in the center of the mold; pre-press the powder-filled mold under a tablet press with a pre-pressing pressure of 5MPa and a pre-pressing time of 5min; assemble the pre-pressed mold with insulating carbon felt with a thickness of 0.5mm, and adjust the mold temperature measuring hole to align with the reserved hole of the insulating carbon felt.

[0054] 3. Spark plasma sintering: Place the graphite mold filled with powder in step 2 in the spark plasma sintering furnace chamber, and evacuate the furnace chamber (10Pa); after starting sintering, heat to 1300℃ at 100℃ / min and keep warm for 10min, then heat to 1600℃ at 100℃ / min and keep warm for 5min; after the insulation is completed, stop heating immediately, cool to room temperature with the furnace, and obtain a tungsten-boron composite material block after demolding (the load borne by the mold during the sintering process is 0.5t).

[0055] Comparative Example 3:

[0056] 1. High-energy mechanical ball milling:

[0057] W powder, B powder and WC carbide balls are loaded into a ball mill, and then an appropriate amount of process control agent anhydrous ethanol is added to the mixed powder; the ball mill is filled with argon and the ball milling parameters are set for ball milling: the ball milling speed is 400 rpm, and the ball milling time is 12 h; the slurry after ball milling is dried to obtain WB composite powder; based on the mass percentage of the mixed powder, the proportion of B powder is 0.5%, and the balance is W powder.

[0058] 2. Powder filling: same as step 2 in Example 3.

[0059] 3. Powder filling: same as step 3 in Example 3.

[0060] See also Figures 1 to 3 As shown, the W-0.5wt.%B composite material prepared by spark plasma sintering in Example 3 can obtain a network second phase pinning structure at the grain boundary, which increases the grain boundary bonding force. The addition of B element also reduces the oxygen content in the matrix material. The oxygen content of the W-0.5wt.%B composite material is 28.3ppm, which is lower than the oxygen content (214.5ppm) of the W-0.5wt.%B composite material prepared by high-energy mechanical ball milling in Comparative Example 3.

[0061] Meanwhile, the W-0.5wt.%B tungsten-based composite material prepared by sintering at 1600°C in Example 3 has a relative density of 96.7% and a microhardness of 506.5±10.9HV, which is better than pure tungsten material (microhardness 360-420HV).

[0062] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a tungsten-based composite material having high hardness, low oxygen content and a network grain boundary pinning structure, characterized in that: Here are the steps: Step 1: Flour making: W powder, B powder and an appropriate amount of WC cemented carbide balls are placed in a plastic solid bottle according to the proportion, filled with argon in a glove box, sealed and placed in a mixer for powder mixing; after mixing, the composite powder is vacuumed and stored to obtain WB composite powder; Step 2: Powder filling: The WB composite powder obtained in step 1 is filled into the graphite mold. Before the mold is filled with powder, carbon paper needs to be rolled evenly, and the carbon paper is tightly attached to the inner wall of the mold, and the distance between the upper and lower punches and the mold is just filled with carbon paper; the upper and lower punches are adjusted so that the powder is located in the center of the mold; the mold filled with powder is pre-pressed under a tablet press; the pre-pressed mold is assembled with thermal insulation carbon felt, and the temperature measuring hole of the mold is adjusted to align with the reserved hole of the thermal insulation carbon felt; Step 3: Spark plasma sintering: The graphite mold filled with the powder in step 2 is placed in a spark plasma sintering furnace chamber, and the furnace chamber is evacuated; sintering is started to prepare a tungsten-boron composite material block, that is, a tungsten-based composite material with high hardness, low oxygen content and a network grain boundary pinning structure.

2. The preparation method according to claim 1, characterized in that In the step 1, the proportion of B powder is 0.5-1.0% by mass, and the remainder is W powder.

3. The preparation method according to claim 1, characterized in that: In the step 1, the argon filling pressure in the plastic solid bottle is 0.01-0.02 MPa.

4. The preparation method according to claim 1, characterized in that: In step 1, the rotation speed of the mixer is 50-60 rpm, and the mixing time of W powder and B powder is 10-15 hours.

5. The preparation method according to claim 1, characterized in that: In step 2, the mold pre-pressing pressure is 5 MPa, and the pre-pressing time is 3 to 5 minutes.

6. The preparation method according to claim 1, characterized in that: The thickness of the assembled carbon felt in step 2 is 0.5 mm.

7. The preparation method according to claim 1, characterized in that: After the furnace chamber is evacuated in step 3, the vacuum degree is 10Pa.

8. The preparation method according to claim 1, characterized in that: The specific steps of spark plasma sintering in step 3 are: heating to 1300°C at 100°C / min and keeping warm for 5-10min, then heating to 1600-1700°C at 100°C / min and keeping warm for 5min; after the insulation is completed, heating is stopped immediately, cooling to room temperature with the furnace, and demolding to obtain a tungsten-boron composite material block.

9. The preparation method according to claim 8, characterized in that: The load borne by the mold during spark plasma sintering is 0.5t.

Citation Information

Patent Citations

  • Preparation method of binary tungsten boride superhard material

    CN107473237A

  • Fine grain powder high-temperature alloy preparation method capable of inhibiting original particle boundary formation

    CN111304476A

  • Preparation method of high-density boron-containing composite material

    CN112779455A

  • Tungsten boride titanium-based nuclear shielding composite material and preparation method thereof

    CN114561569A

  • Boron-enhanced aluminum-containing intermetallic compound bonded tungsten alloy and preparation method thereof

    CN115838877A